PENGARUH KONFLIK KERJA, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP STRES KERJA PEGAWAI PD PASAR KOTA DENPASAR - Kapitan, Agrineh; Kartika Dewi, A. A. Sagung (E-Jurnal Manajemen; Vol 8 No 5 (2019), 2019)
Human resources are the driving force of the company and are the most important asset for the company. The purpose of this study was to explain the effect of work conflict, leadership, and work environment on work stress. The population of this study were all employees in PD. Denpasar Market Badung Market Unit. Sampling in this study using saturated sample or census techniques, where the entire study population will be selected until, so that the number of samples used in this study were 98 employees, excluding 2 leaders in PD. Denpasar City Market Badung Market Unit. Data collected in this study were analyzed using multiple linear regression analysis. The results of the analysis showed that the work conflict had a positive and significant effect while the leadership and work environment had a negative and significant influence on the work stress of employees in PD. Denpasar City Market Badung Market Unit.